The Inhibitory Effects of Herbal Product, CHD-1 Raisin Tree on Methicillin-Resistant Staphylococcus aureus and Food Spoilage Bacteria - นิ่มรัตน์, สุบัณฑิต; แสงส่ง, จำลอง; ขาวผ่อง, วีรสิทธิ์; สุพรรณพันธุ์, พีรพัฒน์; วุฒิพันธุ์ชัย, วีรพงศ์ (KKU Science Journal, 2013)
In this study, the CHD-1 Raisin Tree, a herbal product which derived from plant called Raisin tree and produced in Republic of Korea, was investigated. The two types of product : tablet and capsule, were different for their antibacterial activity against two bacterial groups of Methicillin-resistant Staphylococcus aureus (MRSA) resistant to several antibiotics and spoilage bacteria isolated from dried seafood product (Bacillus coagulans, B. laterosporus, B. licheniformis, Staphylococcus caprae and S. hominis). The activities of two herbal product types were revealed by the agar well diffusion assay. The tablet type dissolved by distilled water showed effective growth inhibition against 5 strains of MRSA and spoilage bacteria with inhibition zone in a range of 10.00 0.00 to 16.70 0.12 mm and 13.30 0.15 to 21.00 0.10 mm, respectively. Whereas, product in capsule type showed no activity against all of the both test MRSA and spoilage bacteria. Therefore, the herbal product, CHD-1 Raisin Tree in tablet type was able to apply as a new effective drug in order to inhibit pathogenic bacteria, especially MRSA, and other bacteria for replacing antibiotics in future.